Precarización del trabajo marítimo: Caso de México. (1980–2006) - López, Alfredo Salazar (Review of International American Studies, 2015)
On Precariousness of Maritime Labor. The Case of Mexico (1980–2006) Currently, the debate on employment and economic performance develops along the lines of two traditional approaches to labor. One side of the debate is represented by the ‘neoclassical’ promoters of the idea that the market is the only factor regulating relations between employers and workers; the other side is represented by institutionalists proposing models for reform of labor markets based on business productivity and competitiveness of nations. However, those occupying the middle ground integrate in their arguments both the need for economic efficiency and the need for social justice, recognizing that forms of state regulation and control in the labor market are necessary. Hence, also the situation of maritime transport is suspended between two systemic assumptions: first, that the regulation of maritime labor should be governed by international standards, with no institutional freedom for each country to design its own rules, and that it should be based on a general model ratified by most nations. Second, compared to the neoclassical model, the present day condition of the shipping industry testifies to the fact that the ‘lack of laws regulating competition is responsible for the serious deterioration of the working conditions’ and that it curtails the space of collective negotiations warranting the seagoing personnel acceptable working conditions. Such a shortage of international regulations renders healthy balance in labor relations impossible. However, despite the present-day diagnosis of the situation, the discussion on the likely paths for the development of labor regulations on board of merchant vessels tends towards arguments presented by the institutionalists, who advocate the need to establish forms of regulation and state control over the market and its players. At present, such a form appears to be the only one leading to the achievement of at least a measure of labor protection at sea. Today, the mechanisms of the market for maritime work impacting the living conditions of the personnel may be seen as exemplified by the phenomenon of the so-called ‘crews of convenience’, i.e.: crews hired under precarious working conditions, which the workers accept seeing no other alternative to unemployment. Such contracts, signed without government or union mediation, in the context in which no international fair trade laws respecting work at sea exist, reinforce the case for national and international regulation. The phenomenon of the crews of convenience and, generally, the intensification of the deregulatory tendencies in the shipping industry, point to the actual as well as potential role of trade unions in the sector. The globalization of shipping has taken unions, born in the context of state regulations, by surprise. The proliferation of free flag shipping and the consequent reduction of national fleets, caused by the liberalization of markets, resulted simultaneously in the increase of the number of sailors hired under substandard conditions and in the growth of the scale of the exchange of goods across the world. The deregulation in this sector allows for both phenomena to expand: on the one hand, it facilitates the free registration of vessels, it energizes the search for tax havens, but on the other, it fosters the free choice in hiring and firing crews and in pricing the freight solely on the basis of the market principles of supply and demand. Exemplifying the situation are the characteristics of the system of labor regulation in Mexico’s maritime labor law, which show that the actual dynamics of the labor market has been accommodated by the system’s flexibility. Yet, it must be noted that this flexibility of flags of convenience effectively undermines the safety of employment for Mexican sailors, because in the context of the reduction of the national fleet, given the precarious conditions of labor, crews must compete with Asians, who make up 80% of the global maritime workforce. To mitigate this situation, efforts have been taken by some nations to find a solution to the problem. Such efforts have been recorded by the International Maritime Organization (IMO) and the International Labour Organisation (ILO), who promote the implementation of international norms and standards of their application. As a result, the Maritime Labour Convention (2006), sponsored by the ILO, has become a milestone in the process leading to improvements in the international working environment. With its working documents amounting to more than 65 conventions and recommendations, its adoption in March 2006 and implemenation on August 21st, 2013, will continue to impact the lives of 1.2 million seafarers in the world, whose work makes 80% of world trade possible. Therefore, it is important to study the effects of the implementation of such regulations in the context of the actual work conditions on board of on ships since international organizations (such as the ILO, which seeks to curb casualization of employment through international rules that protect the interests of workers on board) became active in the process. In this context, the first part of this article illustrates how the merchant navies weaken in the face the processes of economic liberalization (which translates into working conditions on board). In the second part, this phenomenon is studied on the basis of the case of Mexico. Finally, the impact of the 2006 Convention, which aims to address the global maritime job insecurity, is analyzed, with particular emphasis on the prospective consequences of the systematic implementation of the Convention’s regulations of the Convention, whose cornerstone is the protection of the seagoing personnel, yet whose provisions meet with a serious degree of resistance on the part of the advocates of deregulation.